Antioxidant, Antibacterial and Antiproliferative Activities of Areal Parts of Swertia chirata (Bush Ham) Plant Extracts Using In Vitro Models - Ali Raza Naqvi, Syed; Ain, Qurat-Ul-; Ali Khan, Zulfiqar; Hussain, Zaib; Anjum Shahzad, Sohail; Yar, Muhammad; Ghaffar, Abdul; Mahmood, Nasir; Kousar, Samina (Asian Journal of Chemistry, 2013)
Ariel parts of Swertia chirata was investigated for its medicinal values. Like many other plants and herbs, Swertia chirata has also been used for treating diseases particularly liver disorder. Anti-disease functions of most of the plants or herbs extracts have been associated with antioxidant and antibacterial potential. This study was performed to explore the antioxidant and antibacterial activity of the Swertia chirata (Bush ham). This was done by measuring possible constituents responsible for its antioxidant activity such as total phenolic and flavonoid contents. Antioxidant potential was measured using authentic in vitro assay models such as DPPH free radical scavenging assay and per cent inhibition of linoleic acid peroxide. The antibacterial and antiproliferative activity was measured against four different strains of gram positive and gram negative bacteria and MDBK cancer cell line, respectively. Promising concentration of total phenolics and flavonoids resulted encouraging DPPH free radical scavenging (84.32 ± 2.78 and 82.54 ± 3.12 %) and linoleic acid peroxide inhibition (94.04 ± 4.23 and 92.86 ± 4.78 %) and consequently credible antioxidant potential. Antibacterial and antiproliferative data of extracts indicated Swertia chirata might be a good member for fighting against infectious and chronic diseases.